2021
DOI: 10.1155/2021/6360439
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Crude Oil Trade Procurement Model Based on DEA-Malmquist Algorithm

Abstract: To retain valuable information to the maximum extent and enhance the ability to mine the crude oil trade purchase price demand, this paper proposes a crude oil trade purchase model based on the DEA-Malmquist algorithm. The intranet of the management and control platform shall share the same database, and the intranet shall only allow managers to access and manage the system and only allow all registered users to access and realize data exchange between the intranet and the intranet through two-dimensional code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identified submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identified submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a gure unrelated to the topic of the paper and this graph was subsequently identi ed within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scienti c Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identi ed submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a gure unrelated to the topic of the paper and this graph was subsequently identi ed within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scienti c Programming [2][3][4][5][6].…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper, and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identified submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%